Leakage current and surface discharge phenomena : effect on tracking and morphological properties of LLDPE-natural rubber compounds - Piah, M. A. M.; Darus, Ahmad; Hassan, A. (2003)
Polymeric insulators are widely used for high voltage outdoor insulating application due to their substantial advantages compared to the porcelain and glass insulators. Although polymer materials have been proven good, research on development of new polymerbased materials is still on going since the benefits of using polymeric materials are not yet utilised to their full potential. In this work, a new formulated thermoplastic elastomer materials that are composed of linear low-density polyethylene (LLDPE) and natural rubber (NR) filled with different loadings of alumina trihydrate (ATH) fillers is presented. A surface tracking and erosion test is conducted to investigate the characteristics of leakage current on the material surface under the influence of wet contaminated conditions. A computer-based leakage current monitoring system is developed to monitor the leakage current waveform pattern as well as its frequency spectrum. The scanning electron microscope is used to investigate the morphological properties of the materials before and after the tracking test.